Analisis Faktor-Faktor Yang Berhubungan Dengan Kesertaan Akdr/Iud - Sinaga, Masrida (Jurnal Pangan Gizi dan Kesehatan, 2009)
The result of this research shows that most of the respondents have an income ≥ Rp 600.000 (75.0%), high education level (76.0%), sufficient knowledge about IUD (65.0%), sufficient attitude towards IUD (61.0%), sufficient attitude towards health workers (61.0%), sufficient perception towards facilities (62.0%), sufficient accessibility (64.0%), and low family planning counseling. client Result of in-depth interview shows that respondents who do not want to use IUD have some reasons namely they feel shame, afraid during installation, afraid of side effect, expensive, and not available of IUD at health services. Most of the respondents (80.0%) said that IUD method does not contradict religion and local culture. Variables that have significant relationship with the use of IUD at Sub District of Oebobo are income (p=0.021), knowledge about IUD (p=0.0001), attitude towards IUD (p=0.0001), attitude towards health workers (p=0.015), availability of IUD services (p=0.007), accessibility (p=0.004), and counseling of family planning (p=0.0001). Variable of education (p=0.242) does not have significant relationship with the use of IUD. Therefore, it needs to socialize, to promote the tariff of services and superiority of IUD method, and to supply IUD at health services.